2022
DOI: 10.1186/s13046-022-02443-w
|View full text |Cite
|
Sign up to set email alerts
|

CDK7 inhibition augments response to multidrug chemotherapy in pancreatic cancer

Abstract: Background Pancreatic ductal adenocarcinoma (PDAC) is an aggressive cancer with a dismal prognosis. Although combined treatment with gemcitabine and albumin-bound paclitaxel has improved the prognosis of PDAC, both intrinsic and acquired chemoresistance remain as severe hurtles towards improved prognosis. Thus, new therapeutic targets and innovative strategies are urgently needed. Methods In this study, we used the KPC mouse model-derived PDAC cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…CDK7 is detected aberrantly overexpressed in different cancer types (15,16). Several CDK7-selective inhibitors have proved e cacy in various preclinical models of breast (18, 19), pancreatic (20,40), and lung cancer (21) among others. Moreover, some CDK7 inhibitors have entered Phase I clinical trials for breast cancers (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…CDK7 is detected aberrantly overexpressed in different cancer types (15,16). Several CDK7-selective inhibitors have proved e cacy in various preclinical models of breast (18, 19), pancreatic (20,40), and lung cancer (21) among others. Moreover, some CDK7 inhibitors have entered Phase I clinical trials for breast cancers (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing breast cancer TMAs for CDK7 (n = 945), the study found that patients with high-grade and extensive tumors, or those with recurrent disease, exhibited lower CDK7 expression. Elevated CDK7 levels were instead associated Breast cancer [70], Gastric cancer [54], Osteosarcoma [115], Synovial sarcoma [116], Thyroid carcinoma [117], T cell acute lymphoblastic leukemia [118] No [95], Head and neck squamous cell carcinoma [121], Thyroid cancer [122], Neuroblastoma [123], Glioblastoma [124], Gastrointestinal stromal tumours [125], Pancreatic cancer [126], Hepatocellular carcinoma [127], Gallbladder cancer [39], Cholangiocarcinoma [128], Colorectal cancer [40], Nasopharyngeal carcinoma [129], Prostate cancer [130], Renal cell carcinoma [131], Urothelial carcinoma [132], Bladder cancer [133], Melanoma [134], Osteosarcoma [135], lymphomas [62], Leukemia [43] No with extended BCSS and prolonged time to distant metastasis [67]. This landscape of disparate findings illustrates the complexity of CDK7's role within breast cancer prognosis and highlights the necessity for further refined and targeted investigations.…”
Section: The Expression Of Cdk7 and Its Prognostic Value In Breast Ca...mentioning
confidence: 99%
“…Indeed, SY-351, a highly selective irreversible CDK7 inhibitor showed a potent effect in splicing modulation 25 . Of note, CDK7 has emerged as a target to address chemoresistance, as revealed by a recent kinome-wide CRISPR-Cas9 loss-of-function screening conducted in the PDAC cell line derived from the KPC mouse model 26 .…”
Section: Introductionmentioning
confidence: 99%